Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Discover the answers you need from a community of experts ready to help you with their knowledge and experience in various fields. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
Sure! Let's work through this step by step.
### Part (i): Verifying [tex]\( m - n \neq n - m \)[/tex]
Given values:
[tex]\[ m = -\frac{7}{9} \][/tex]
[tex]\[ n = \frac{5}{6} \][/tex]
First, let's calculate [tex]\( m - n \)[/tex]:
[tex]\[ m - n = -\frac{7}{9} - \frac{5}{6} \][/tex]
To subtract these fractions, we need a common denominator. The least common multiple (LCM) of 9 and 6 is 18.
Convert each fraction to have the denominator 18:
[tex]\[ -\frac{7}{9} = -\frac{7 \times 2}{9 \times 2} = -\frac{14}{18} \][/tex]
[tex]\[ \frac{5}{6} = \frac{5 \times 3}{6 \times 3} = \frac{15}{18} \][/tex]
Now subtract these fractions:
[tex]\[ m - n = -\frac{14}{18} - \frac{15}{18} = -\frac{14 + 15}{18} = -\frac{29}{18} \][/tex]
Next, let's calculate [tex]\( n - m \)[/tex]:
[tex]\[ n - m = \frac{5}{6} - (-\frac{7}{9}) \][/tex]
Rewriting [tex]\(-(-\frac{7}{9})\)[/tex]:
[tex]\[ n - m = \frac{5}{6} + \frac{7}{9} = \frac{5 \times 3}{6 \times 3} + \frac{7 \times 2}{9 \times 2} = \frac{15}{18} + \frac{14}{18} = \frac{29}{18} \][/tex]
We obtained:
[tex]\[ m - n = -\frac{29}{18} \][/tex]
[tex]\[ n - m = \frac{29}{18} \][/tex]
Clearly, [tex]\( m - n \)[/tex] and [tex]\( n - m \)[/tex] are not equal, thus:
[tex]\[ m - n \neq n - m \][/tex]
Verification (i) is true.
### Part (ii): Verifying [tex]\( -(m + n) = (-m) + (-n) \)[/tex]
First, compute [tex]\( m + n \)[/tex]:
[tex]\[ m + n = -\frac{7}{9} + \frac{5}{6} \][/tex]
Using the common denominator 18:
[tex]\[ -\frac{7}{9} = -\frac{14}{18} \][/tex]
[tex]\[ \frac{5}{6} = \frac{15}{18} \][/tex]
Add these fractions:
[tex]\[ m + n = -\frac{14}{18} + \frac{15}{18} = \frac{-14 + 15}{18} = \frac{1}{18} \][/tex]
Now, compute [tex]\( -(m + n) \)[/tex]:
[tex]\[ -(m + n) = -\left( \frac{1}{18} \right) = -\frac{1}{18} \][/tex]
Next, compute [tex]\( (-m) + (-n) \)[/tex]:
[tex]\[ -m = -\left( -\frac{7}{9} \right) = \frac{7}{9} \][/tex]
[tex]\[ -n = -\left( \frac{5}{6} \right) = -\frac{5}{6} \][/tex]
Using the common denominator 18 again:
[tex]\[ \frac{7}{9} = \frac{14}{18} \][/tex]
[tex]\[ -\frac{5}{6} = -\frac{15}{18} \][/tex]
[tex]\[ (-m) + (-n) = \frac{14}{18} - \frac{15}{18} = \frac{14 - 15}{18} = -\frac{1}{18} \][/tex]
Therefore:
[tex]\[ -(m + n) = -\frac{1}{18} \][/tex]
[tex]\[ (-m) + (-n) = -\frac{1}{18} \][/tex]
Since both are equal:
[tex]\[ -(m + n) = (-m) + (-n) \][/tex]
Verification (ii) is true.
In summary:
(i) [tex]\( m - n \neq n - m \)[/tex] is verified as true.
(ii) [tex]\( -(m + n) = (-m) + (-n) \)[/tex] is verified as true.
### Part (i): Verifying [tex]\( m - n \neq n - m \)[/tex]
Given values:
[tex]\[ m = -\frac{7}{9} \][/tex]
[tex]\[ n = \frac{5}{6} \][/tex]
First, let's calculate [tex]\( m - n \)[/tex]:
[tex]\[ m - n = -\frac{7}{9} - \frac{5}{6} \][/tex]
To subtract these fractions, we need a common denominator. The least common multiple (LCM) of 9 and 6 is 18.
Convert each fraction to have the denominator 18:
[tex]\[ -\frac{7}{9} = -\frac{7 \times 2}{9 \times 2} = -\frac{14}{18} \][/tex]
[tex]\[ \frac{5}{6} = \frac{5 \times 3}{6 \times 3} = \frac{15}{18} \][/tex]
Now subtract these fractions:
[tex]\[ m - n = -\frac{14}{18} - \frac{15}{18} = -\frac{14 + 15}{18} = -\frac{29}{18} \][/tex]
Next, let's calculate [tex]\( n - m \)[/tex]:
[tex]\[ n - m = \frac{5}{6} - (-\frac{7}{9}) \][/tex]
Rewriting [tex]\(-(-\frac{7}{9})\)[/tex]:
[tex]\[ n - m = \frac{5}{6} + \frac{7}{9} = \frac{5 \times 3}{6 \times 3} + \frac{7 \times 2}{9 \times 2} = \frac{15}{18} + \frac{14}{18} = \frac{29}{18} \][/tex]
We obtained:
[tex]\[ m - n = -\frac{29}{18} \][/tex]
[tex]\[ n - m = \frac{29}{18} \][/tex]
Clearly, [tex]\( m - n \)[/tex] and [tex]\( n - m \)[/tex] are not equal, thus:
[tex]\[ m - n \neq n - m \][/tex]
Verification (i) is true.
### Part (ii): Verifying [tex]\( -(m + n) = (-m) + (-n) \)[/tex]
First, compute [tex]\( m + n \)[/tex]:
[tex]\[ m + n = -\frac{7}{9} + \frac{5}{6} \][/tex]
Using the common denominator 18:
[tex]\[ -\frac{7}{9} = -\frac{14}{18} \][/tex]
[tex]\[ \frac{5}{6} = \frac{15}{18} \][/tex]
Add these fractions:
[tex]\[ m + n = -\frac{14}{18} + \frac{15}{18} = \frac{-14 + 15}{18} = \frac{1}{18} \][/tex]
Now, compute [tex]\( -(m + n) \)[/tex]:
[tex]\[ -(m + n) = -\left( \frac{1}{18} \right) = -\frac{1}{18} \][/tex]
Next, compute [tex]\( (-m) + (-n) \)[/tex]:
[tex]\[ -m = -\left( -\frac{7}{9} \right) = \frac{7}{9} \][/tex]
[tex]\[ -n = -\left( \frac{5}{6} \right) = -\frac{5}{6} \][/tex]
Using the common denominator 18 again:
[tex]\[ \frac{7}{9} = \frac{14}{18} \][/tex]
[tex]\[ -\frac{5}{6} = -\frac{15}{18} \][/tex]
[tex]\[ (-m) + (-n) = \frac{14}{18} - \frac{15}{18} = \frac{14 - 15}{18} = -\frac{1}{18} \][/tex]
Therefore:
[tex]\[ -(m + n) = -\frac{1}{18} \][/tex]
[tex]\[ (-m) + (-n) = -\frac{1}{18} \][/tex]
Since both are equal:
[tex]\[ -(m + n) = (-m) + (-n) \][/tex]
Verification (ii) is true.
In summary:
(i) [tex]\( m - n \neq n - m \)[/tex] is verified as true.
(ii) [tex]\( -(m + n) = (-m) + (-n) \)[/tex] is verified as true.
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.